The Impact of Good Corporate Governance on Financial Distress in Transportation Sector Companies in Indonesia - Patriandari Patriandari; Rianto Rianto; Annisa Ristianti (Quantitative Economics and Management Studies, 2023)
This study aims to determine the influence of the Board of Directors, Institutional Ownership, and Managerial Ownership on Financial Distress in Transportation Subsector Companies Listed on the Indonesia Stock Exchange for the 2018-2020 Period. This study used a sample of 29 companies from the Transportation Subsector for 3 periods using the purposive sampling method. The independent variables in this study are the board of directors as measured by calculating the number of members of the board of directors in the relevant year period, institutional ownership as measured by dividing the number of shares held institutionally by the number of shares outstanding, and managerial ownership measured by dividing the number of shares held by management by the number of shares outstanding. Meanwhile, the dependent variable in this study is financial distress as measured by the altman z-score method. The results of this study show that: (1) The board of directors has no effect on the occurrence of financial distress. (2) Institutional ownership negatively affects the occurrence of financial distress. (3) Managerial ownership negatively affects the occurrence of financial distress.